People are asking... Is this the end? : signs of God's providence in a disturbing new world - Jeremiah, David, 1941-; Turning Point (Broadcast ministry) (Nashville, Tennessee, W Publishing Group, 2016)
Never have the headlines been this jarring, the cultural changes this rapid, or the moral decay this pronounced. What on earth is happening? After each new occurrence, the most oft-heard questions are, "Will the world ever be the same again?" and "Where is God in all of this?" Turning Point founder Dr. David Jeremiah specializes in topics that deal with biblical application and modern culture. The time has come to accept this new normal, Jeremiah says, and understand how God's hand is still at work on His eternal plan for mankind. No one can afford to ignore these warnings, but all can better understand the greater story and the role we each play in this changing world. From prophetic clues in Scripture to an understanding of the power of Christ in all believers, this book directs us on a clear path forward--
Part I: Is this the end for America? The age of anything goes -- The bleeding of our borders -- The increase of intolerance -- The apathy of America -- The remedy of revival -- Part II: Is this the end for the world? The isolation of Israel -- The insurgency of ISIS -- The resurrection of Russia -- The rapture of the redeemed -- Translated before the Tribulation.
Includes bibliographical references (pages 297-321).
Keywords: Bible -- Criticism, interpretation, etc; End of the world; Christian life